Public knowledge and attitudes towards antibiotics and antimicrobial resistance (AMR) in vietnam: a cross-sectional study - Van Nhi Tran; Thuc Quyen Huynh; Pham Tuyet Nhi Nguyen; Thi Phuong Truc Nguyen; Hoang An Nguyen; Gregory Hurter; Si Tuan Nguyen; Minh Khoi Le; Minh Thong Le; Chan Khon Huynh; Phuong Thao Nguyen; Thi Thu Hoai Nguyen (Antimicrobial Stewardship & Healthcare Epidemiology, 2025)
Abstract